МНОГОКРИТЕРИАЛЬНЫЙ СИНТЕЗ АНИЗОТРОПИЙНЫХ РЕГУЛЯТОРОВ МНОГОМАССОВЫХ ЭЛЕКТРОМЕХАНИЧЕСКИХ СИСТЕМ - Кузнецов , Б.И.; Никитина , Т.Б.; Татарченко , М.О.; Хоменко, В.В. (Інститут електродинаміки НАН України, Київ, 2014)
The problem of multicriterion anisotropic regulators synthesis by multimass electromechanical systems and the possibility of its solution based on the concept of multi- functional accessory of the state vector that can satisfy various requirements that apply to the work of multimass electromechanical systems in different modes. Proved and developed a method of selecting the matrices with which formed the target vector stochastic robust control by solving a nonlinear programming problem. Minimizing the anisotropic norm of a stochastic system provides a minimum sensitivity of the synthesized system to modify the plant models and external influences. The results of experimental studies of two-mass electromechanical system showed that the use of synthesized anisotropic regulators compared with standard controls has reduced the time of the first agreement by five times, to increase the smoothness of motion at low speeds by 1.7 times, to reduce the variance of the random errors mining master control four times. References 5.